1869 Ariz. Sess. Laws 33 - (:unkn) unknown (My University, 1868)
Any person or persons within this Territory who shall sell or give arms or ammunition to any Indians, or repair arms for them, shall, upon conviction thereof, be punished as follows .
Keywords: ENSLAVED PERSONS & OTHER MINORITIES